Pembelajaran Sains Dalam Desain Pendekatan Tematik Integratif - suhendi suhendi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2014)
Children who are in the early elementary classroom are children who are at an early age range. Early childhood period is a short time but it is a very important period in one's life. Therefore, at this time the full potential of the child should be encouraged so that it will develop optimally. Therefore, it is necessary to develop an approach to learning that is more appropriate to the child's level of cognitive development, One approach that can be used in low- grade teaching in particular is an integrated thematic approach. One of the advantages of thematic learning is holistic in nature. Holistic nature is in accordance with the level of cognitive development of children, and also relefan with science learning pattern that requires integrity and coherence (holistic). So the design of learning science with a thematic approach dinyakini will provide an effective influence on the process of learning is done.